Hypoxia and Anoxia - Das, Kusal K.; Shivanagouda Biradar, Mallanagouda (IntechOpen, 2018)
The molecular deprivation of oxygen is manifested by hypoxia, a deficiency of oxygen and anoxia, or the absence of oxygen supply to the tissues. This book entitled Hypoxia and Anoxia will cover a broad range of understanding on hypoxia and anoxia from molecular mechanisms to pathophysiology. Hypoxia and anoxia stimulate multiple systems through specific cell signal transduction pathways and regulate several transcriptional factors like HIF-1, REST to encode genes for VEGF, Epo, etc. This book will also highlight different types of hypoxia and anoxia along with their impact on apoptosis, cardiovascular pathophysiology, and glucose regulatory mechanisms. This book will be a ready reckoner to give a deep understanding of the oxygen-sensing environment in vivo for researchers, academicians, and clinicians throughout the world.